Hồ Chí Minh, nhà mác xít sáng tạo của Đảng và cách mạng Việt Nam - Mạch, Quang Thắng (2011)
Tác giả: Mạch Quang Thắng, GS,TS; Phạm Ngọc Anh, PGS,TS; Trần Văn Hải, TS; Nguyễn Thanh Tuấn, PGS,TS -- Từ khóa: Tư tưởng Hồ Chí Minh